Sandwich Technique for Endovascular Repair of Acute Type A Aortic Dissection. (October 2017) - Gao, Feng; Zeng, Qian; Lin, Fangming; Ge, Xiaohu
Overview: To describe a new endovascular procedure for acute type A aortic dissection (TAAD) repair.Methods: Between 2013 and 2016, 12 patients (average age 54±9.6 years; 10 men) with acute TAAD (mean EURO score 11.4%±3.2%, range 5–17) and unfit for surgery underwent thoracic endovascular aortic repair (TEVAR) with 2 periscope grafts to preserve blood supply to supra-aortic branches plus bypass grafting as needed. If the ascending aorta was dilated to >40 mm, sternotomy was performed to wrap the ascending aorta and reduce its diameter to accommodate the aortic stent-grafts.Results: All patients were successfully treated. Seven patients required bypass grafting, and most of the patients had periscope grafts to the innominate/right common carotid artery and left common carotid artery; only 3 patients had the left subclavian artery preserved. All patients exhibited good hemodynamics and normal pressures after the procedure. The mean procedure time and blood loss were 4.5±1.0 hours and 217±111.5 mL, respectively. Two patients treated emergently died shortly after surgery from multiorgan failure. The average follow-up duration was 17±14.5 months (range 2–42) in the 10 survivors. The remaining patients recovered and none experienced stent-graft thrombosis, stroke, or peripheral artery embolism during follow-up.Conclusion: A procedure that combines sandwich/periscope grafting with TEVAR, wrapping of the aorta, and supra-arch bypass grafting can be used to treat patients with acute TAAD.